2012
DOI: 10.1007/s13311-011-0102-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Nonpharmacological Management of Delirium in Critically Ill Patients

Abstract: Delirium is a common yet under-diagnosed syndrome of acute brain dysfunction, which is characterized by inattention, fluctuating mental status, altered level of consciousness, or disorganized thinking. Although our recognition of risk factors for delirium has progressed, our understanding of the underlying pathophysiologic mechanisms remains limited. Improvements in monitoring and assessment for delirium (particularly in the intensive care setting) have resulted in validated and reliable tools such as arousal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 159 publications
0
83
0
11
Order By: Relevance
“…These include proactive geriatric consultation [9] and education of medical and nursing staff with special attention to known risk factors [10,11]. In ICU patients, non-pharmacological measures have hardly been studied in relation to delirium [12]. Still, the ICU environment with continuous light and noise, around the clock personnel and lack of orientation points is assumed to play a role in the development of delirium [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include proactive geriatric consultation [9] and education of medical and nursing staff with special attention to known risk factors [10,11]. In ICU patients, non-pharmacological measures have hardly been studied in relation to delirium [12]. Still, the ICU environment with continuous light and noise, around the clock personnel and lack of orientation points is assumed to play a role in the development of delirium [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In ICU patients, non-pharmacological measures have hardly been studied in relation to delirium [12]. Still, the ICU environment with continuous light and noise, around the clock personnel and lack of orientation points is assumed to play a role in the development of delirium [12][13][14][15]. A previous study in ICU patients suggested that isolation and the absence of daylight were associated with an increased risk of delirium [13].…”
Section: Introductionmentioning
confidence: 99%
“…This is has been achieved by identifying modifiable risk factors and minimizing them safely. As summarized in recent reviews and reports [16][17][18][19], the incidence and/or duration of delirium in mechanically ventilated ICU patients can be reduced in multiple ways, specifically (a) managing agitation with light sedation using dexmedetomidine (a centrally acting a2 adrenergic agonist), not benzodiazepines (GABA A receptor modulators) apart from some exceptional circumstances [ [16][17][18]. Nevertheless, the occurrence and duration of delirium in mechanically ventilated ICU patients remains high [18].…”
mentioning
confidence: 99%
“…Asimismo, los α-2 agonistas (clonidina y dexmedetomidina) podrían también ser opciones para el manejo de pacientes (35,36,37) críticamente enfermos .…”
Section: Otros Fármacos Potenciales Para El Deliriumunclassified